Smoking cessation counselling training in the pre-clerkship curriculum of Canadian medical schools: A national survey (Canadian Medical Education Journal, 2018)
Background: Cigarette use is Canada’s leading cause of preventable disease, disability, and death. The Medical Council of Canada requires that physicians be able to address tobacco-use, however smoking cessation counselling (SCC) training remains largely neglected in the pre-clerkship curricula of many Canadian medical schools.Methods: Between July and October of 2015, Canada’s 17 medical schools were invited to participate in an administrative survey: The Canadian Medical School Assessment of Smoking Cessation Counselling in the Pre-Clerkship Curriculum. Each was asked to comment on the presence of 28 tobacco-related topics in their curricula, including: time devoted to source material; year(s) of training during which medical students were exposed to related content; methods of teaching and examination; and, the attitudes, policies, and barriers relevant to the presence of smoking cessation counselling (SCC) training in the curriculum.A second short survey: Assessing Medical Students Attitudes toward Smoking Cessation Education was distributed to 100 University of Ottawa medical students to assess comfort level and perceived confidence toward addressing smoking cessation with patients.Results: Eleven of 17 medical schools completed the administrative survey. The results demonstrated substantial deficits and inconsistencies in the delivery of SCC training in the pre-clerkship curricula of Canada’s medical schools.  The short survey revealed perceived discomfort regarding smoking cessation discussion, consistent with the potential curriculum deficits suggested in the larger national survey.Conclusion: The results of both surveys suggest an unfortunate oversight given the devastating impact of tobacco-related diseases. Institutional commitment and enhanced inter-university collaboration could facilitate the development of a national undergraduate medical education program to enhance the delivery of SCC training within the pre-clerkship curricula of Canadian medical schools.